Efficacy of non-antibiotic treatment options for digital dermatitis on an organic dairy farm. (January 2020) - Paudyal, S.; Manriquez, D.; Velasquez, A.; Shearer, J.K.; Plummer, P.J.; Melendez, P.; Callan, R.J.; Sorge, U.S.; Bothe, H.; Velez, J.; Pinedo, P.J.
Highlights: Digital dermatitis is a painful condition that can result in lameness and decreased performance. Two non-antibiotic formulations resulted in earlier transition to M0 lesions than no treatment. A copper sulphate and iodine combination was most effective in reducing lesion size, pain, and lameness. A honey and iodine combination reduced lesion size but effects were transient. Abstract: The objective of this study was to evaluate the efficacy of two non-antibiotic treatment options for digital dermatitis (DD) on an organic certified dairy farm. A randomized clinical trial was conducted using 70 multiparous Holstein cows with an early DD lesion at a USDA certified organic dairy farm in Northern Colorado, USA. Cows were enrolled in the study based on the presence of early DD lesions (scores M1 and M2) and randomly assigned to one of three treatments: (1) topical application of copper sulfate and iodine (CUI); (2) topical application of honey and iodine (HOI); and (3) control subject to no treatment (CON). Cows were evaluated at enrolment and on days 3, 12, 28, and 120 post treatment for pain and lesion size and received a locomotion and a lesion score. Cure was defined as the transition from active to non-active stages (M1/M2 to M0 or M4). The formulations had variable effects on the treatment of DD. The cure rate was numerically higher for CUI on all follow up days. The proportion of cows experiencing pain on d3 after treatment was greater in CON, followed by HOI and CUI. However, this proportion increased in HOI during the follow up period. The CUI group had a greater reduction in lesion size and larger lesions persisted in HOI. Non-antibiotic treatment formulations were partially effective in the treatment of DD in organic dairy cows: The two non-antibiotic formulations resulted in an earlier transition to mature lesions compared with the control group. The CUI combination was the most effective treatment in reducing lesion size, pain, and lameness in affected cows. However, this combination had short-term efficacy, which did not persist throughout the duration of the study. The HOI combination produced only transient reduction in lesion size.